Influence of Surface Polarity on Optoelectronic Properties of PEDOT:PSS/ZnO Hybrid Heterojunctions. Issue 6 (15th January 2021) - Yatskiv, Roman; Grym, Jan; Tiagulskyi, Stanislav; Bašinová, Nikola
Abstract : The influence of polar and nonpolar crystallographic orientations of ZnO substrates on the current transport mechanism in poly(3, 4‐ethylenedioxythiophene) poly(4‐styrenesulfonate) (PEDOT:PSS)/ZnO heterojunctions is investigated by DC and AC electrical measurements. It is shown that PEDOT:PSS forms high‐quality rectifying junctions on nonpolar planes of n‐type ZnO substrates, whereas on polar c ‐planes, the quality of the junction is affected by the surface polarity, with lower‐quality junctions formed on the O‐polar c ‐plane. The lower quality of the junction is attributed to partial degradation of the O‐polar surface caused by the acidic nature of PEDOT:PSS. By the analysis of current–voltage characteristics, it is demonstrated that the recombination‐tunneling mechanism dominates charge transport in the forward direction. An equivalent circuit is proposed to interpret the data obtained by impedance spectroscopy and the parameters of the equivalent circuit are extracted. Abstract : Herein it is demonstrated that electrical properties of poly (3, 4‐ethylenedioxythiophene) poly(4‐styrenesulfonate) (PEDOT:PSS)/ZnO Schottky junctions strongly depend on the crystallographic orientation of the ZnO substrate. PEDOT:PSS forms high‐quality rectifying junctions on nonpolar planes of n ‐type ZnO substrates, whereas on polar c ‐planes, the quality of the junction is affected by the surface polarity, with lower‐quality junctions formed on the O‐polar c ‐plane.